A produção do espaço e a relação rural urbano : do Movimento dos Trabalhadores Desempregados (MTD), em Vitória da Conquista - BA - Menezes, Hilário José (2011)
This research aims to discuss and analyze the process of territorialization of the Movimento dos Trabalhadores Desempregados (MTD) and the rural / urban connexion, with the object of study the social subjects who participate in the MTD, in Vitória da Conquista, Bahia, directly affected by unemployment and homelessness. Establishing a counterpoint to the current economic model, some organized social movements fighting for the democratization of access to land and believe that only land reform can solve this problem. As a research methodology, this study used the critical-dialectical method, the life history, and discourse analysis as a tool for analysis of data collected through participant observation, field diary, recording descriptive and semi-structured interviews. Specifically, we analyzed the Settlement Zumbi dos Palmares, located in Vitória da Conquista, Bahia, realized from the political struggle implemented by the MTD. The results indicate that the MTD was inspired by the debates established by Consulta Popular to implement the goals of struggle, based on the creation of spaces and collective projects from the reality experienced by people priced out of access to land and employment. Furthermore, we observed that the history of struggle is part of the MTD of the contemporary context of the implementation of housing policies for low income and who live in risk areas. It follows therefore that the social pressure exerted by social movements shows to society and to the needs of public housing and work for a portion of society living in precarious conditions.